Characterisation of tool shape and rotational speed for increased speed during friction stir welding of AA2024-T3. (January 2015) - Trimble, D.; O'Donnell, G.E.; Monaghan, J.
Abstract: A combination of tool force monitoring and post weld assessment has been used to determine effective welding parameters for the production of good quality friction stir welds at the highest possible welding speeds. Results indicate that it is possible to achieve good weld quality at speeds up to 355 mm/min by welding with a scroll shoulder and triflute pin at a rotational speed of 450 rpm. Welds produced at this speed achieved a tensile strength of 93.9% of that of the parent material with relatively good ductility (8.5% tensile elongation) and the presence of no internal or surface defects.